TP53 Mutations in Human Cancer: Database Reassessment and Prospects for the Next Decade - Leroy, Bernard; Anderson, Martha; Soussi, Thierry (Human mutation, 2014)
ABSTRACT More than 50% of human tumors carry TP53 gene mutations and in consequence more than 45,000 somatic and germline mutations have been gathered in the UMD TP53 database (http://p53.fr). Analyses of these mutations have been invaluable for bettering our knowledge on the structure–function relationships within the TP53 protein and the high degree of heterogeneity of the various TP53 mutants in human cancer. In this review, we discuss how with the release of the sequences of thousands of tumor genomes issued from high‐throughput sequencing, the description of novel TP53 mutants is now reaching a plateau indicating that we are close to the full set of mutants that target the elusive tumor‐suppressive activity of this protein. We performed an extensive and thorough analysis of the TP53 mutation database, focusing particularly on specific sets of mutations that were overlooked in the past because of their low frequencies, for example, synonymous mutations, splice mutations, or mutations‐targeting residues subject to posttranslational modifications. We also discuss the evolution of the statistical methods used to differentiate TP53 passenger mutations and artifactual data from true mutations, a process vital to the release of an accurate TP53 mutation database that will in turn be an invaluable tool for both clinicians and researchers. Frequency of cancer deaths worldwide and relationship to the frequency of TP53 mutations.